Characterization of a Novel Ti-PVDF membrane performance in membrane bio-reactors - Ng, Ze Xuan (Nanyang Technological University, 2021)
In recent years, the use of submerged membrane bioreactors (MBR) are regarded as a superior alternative to conventional activated sludge processes in wastewater treatment plants. Of which, hollow fibre membranes are most commonly used due to its high packing density and flexibility. The ever increasing quantities of wastewater makes MBR an ideal option when land scarcity are of concern. The lifespan and durability of membranes poses great importance to the system’s operation and maintenance. Hence, this study aims to focus on characterizing a novel hollow fibre membrane performance in a designed submerged MBR system. The use of 2 other commercially available membranes serves as a benchmark for the novel Ti-PVDF membrane under in controlled environments with similar operating parameters. The study comprises of five phases; membrane characterization, membrane bioreactor (MBR) design and setup, preliminary result testing, long-term cycle operations and identifying the effects of chemical oxidation on membranes. The initial phase involves the study of the membranes’ physical, mechanical and chemical properties. The second phase focuses on the design of a lab bench submerged anoxic-aerobic-oxidation MBR setup capable of treating synthetic wastewater. Operational parameters were adjusted to optimize the removal of organics, nitrogen and turbidity. Preliminary testing of the membranes was conducted with an ON: OFF cycle of 23: 1 hours to accelerate membrane fouling under prolong hours of operation. The fourth stage introduces a 50 day running cycle operating with intervals of 9: 1 mins, replicating full scale treatment plant operations. In addition, a high mixed liquor suspended solid concentrations were maintained at 8g/L. Finally, membrane characterization methods were carried out on the fouled membrane to evaluate the effect of chemical oxidation.